UiTM inked MoU with five universities in China - Chung, Ellen (UiTM Sarawak, 2020)
Professor Dato Dr. Jamil Hamali, Rector of UiTM Sarawak Branch, signed Memorandums of Understanding with five public universities in China on behalf of Vice Chancellor Emeritus Professor. Ir. Dr. Azraai Kassim, between 9 and 13 September 2019. The five universities were China Pharmaceutical University (CPU) in Nanjing, Jiangsu University (JSU) in Jiangsu, Anhui University (AHU) and Anhui Medical University (AHMU) both in Hefei, as well as Beijing Wuzi University (BWU) in Beijing. Also present at these signing ceremonies were Deputy Rector Associate Professor Dr. Firdaus Abdullah, Professor Dr Khong Heng Yen and Coordinator for Office of International Affairs, Dr Ellen Chung.